Ecological and economic impacts of ocean deoxygenation on Pacific halibut fisheries: A multidisciplinary assessment of projected losses - Hongsik Kim; Louise Teh; Ilyass Dahmouni; Lubna Alam; Ibrahim Issifu; U. Rashid Sumaila (Ecological Economics, 2026)

Mangroves as land and ocean buffers: A comparative analysis of mangrove ecosystem services in Ghana and Tanzania - Ibrahim Issifu; Menelisi Falayi; Terry Sunderland; U. Rashid Sumaila (Ocean & Coastal Management, 2026)

Genetic parameter estimates and selection gain for multiple traits in white Guinea yam (Dioscorea rotundata) in Ghana - Kwabena Darkwa; Emmanuel Amponsah Adjei; Emmanuel B. Chamba; Alhassan Sayibu; Isaac Kodzo Amegbor; Freda Ansaah Agyapong; Ziblila Sayibu; Ibrahim Sayibu; Martain Kangmennaang; Muazu Issifu; Paterne A. Agre; Patrick Adebola; et al. (Euphytica, 2025)
Quantifying selection gains enables a more targeted assessment of breeding program effectiveness, highlighting opportunities for strategic improvement and optimized genetic advancement in white Guinea Yam. This study assessed genetic parameters and gain for key traits in a white Guinea yam ( D. rotundata ) breeding population. A total of 81 genotypes were evaluated for two seasons using a 9 × 9 lattice design with three replicates. Data was collected on yam mosaic virus disease severity, tuber yield and tuber dry content for genetic analysis. Broad sense heritability was generally high (> 60) for most of the traits. At the same time, the corresponding genetic advance as a percentage of the mean was exceptionally high (30.28–93.96%) for tuber yield, tuber flesh oxidation, average tuber weight and number of tubers per plant, suggesting additive genetic effects. A multi-trait selection index of the 5% highest performing genotypes revealed positive genetic gain for plant vigour, tuber length, and width, tuber weight per plant, average tuber weight and fresh tuber yield. The genetic gain was, however, negative for tuber dry matter content compared to the check varieties, necessitating a modification of the current breeding scheme such that post-harvest food quality is not sacrificed for tuber yield. Ranking of the breeding lines based on the multi-trait selection index identified four lines (TDr1700004_014, TDr1700004_113, TDr1700001_112 and TDr1700002_090) with high genetic merits for all the economic traits. These lines can be used as potential trait progenitors and evaluated further for possible release as new varieties. Our results decipher the genetic control and provide an overview of the performance of the breeding program for key traits in white Guinea yam.

Assessing the ecological and economic transformation pathways of plastic production system - Ibrahim Issifu; Ilyass Dahmouni; U. Rashid Sumaila (Journal of Environmental Management, 2025)

Plastics’ circular economy for the Galápagos Islands? Exploring plastics governance with implications for social and ocean equity in a UNESCO World Heritage Site - Juan José Alava; María José Barragán-Paladines; Jessica Vandenberg; Gabriela Alonso-Yanez; Marcia Moreno-Báez; Nastenka Calle; Judith Denkinger; Ibrahim Issifu; Eduardo Espinoza; Nikita Gaibor; Mauricio Velásquez; Andrés M. Cisneros-Montemayor (Frontiers in Marine Science, 2025)

Rethinking blue economy governance – A blue economy equity model as an approach to operationalise equity - Freya Croft; Hugh Breakey; Michelle Voyer; Andrés Cisneros-Montemayor; Ibrahim Issifu; Makrita Solitei; Catherine Moyle; Brooke Campbell; Kate Barclay; Dominque Benzaken; Hekia Bodwitch; Leah Fusco; et al. (Environmental Science & Policy, 2024)

Aquaculture over-optimism? - U. Rashid Sumaila; Andrea Pierruci; Muhammed A. Oyinlola; Rita Cannas; Rainer Froese; Sarah Glaser; Jennifer Jacquet; Brooks A. Kaiser; Ibrahim Issifu; Fiorenza Micheli; Rosamond Naylor; Daniel Pauly (Frontiers in Marine Science, 2022)
The recent rapid growth in aquaculture production reported by the United Nations Food and Agriculture Organization may have inadvertently generated what we denote here as aquaculture over-optimism. An extreme form of this is the notion that we need not worry about sustaining wild fish stocks because we can meet the global need through farming. Here we investigate whether the recent growth in aquaculture production can be maintained, and we compare aquaculture production projections with the future need for fish to find out whether aquaculture over-optimism can be justified. We show relevant evidence suggesting that aquaculture growth rates in all the cases studied have already reached their peak and have begun declining. Also, our results indicate that without wild fish, the world will face a fish food shortage of about 71 million tonnes annually by 2030, and the aquaculture production growth rate would have to be 3 times current average projected production by the FAO, the World Bank and the OECD in 2030. Finally, the current geographical distribution of farmed fish production suggests that even if aquaculture over-optimism is physically, economically, technically and ecologically feasible, its socio-economic cost to low-income coastal countries could be devastating.

Impact of Ocean Warming, Overfishing and Mercury on European Fisheries: A Risk Assessment and Policy Solution Framework - Ibrahim Issifu; Juan José Alava; Vicky W. Y. Lam; U. Rashid Sumaila (Frontiers in Marine Science, 2022)
Previous studies have shown that multiple-environmental stressors are expected to have significant and geographically differential impacts on the health and abundance of marine species. In this paper, we analyze the combined impacts of ocean warming, overfishing and mercury pollution in European waters by projecting the impacts of climatic and non-climate drivers on marine species in European waters. Our findings suggest that the impacts vary widely depending on different species and their mean temperature tolerance (MTT). We find for instance, that more than 5 temperate benthopelagic species including, bobtail squids ( Sepiida) frogfishes ( Lophius) great Atlantic scallop ( Pecten maximus) red mullet ( Mullus barbatus barbatus) and common octopus ( Octopus vulgaris) are affected (i.e., weakens their resilience to climate change) by the increase in sea surface temperature (SST) under RCP 8.5 in 2050 and 2100. Mercury contamination was estimated to increase in some species (e.g., ∼50% in swordfish), exceeding mercury consumption guideline thresholds (>1 mg/kg). This negative impact may limit the capacity of fisheries and marine ecosystem to respond to the current climate induced pollution sensitivity. An implication of our study is that the international community should strengthen a global ban on mercury emissions under the mandate of the Minamata Convention, comparable to the United Nations framework for persistent organic pollutant emission sources. Ongoing global efforts aimed at minimizing carbon footprint and mercury emissions need to be enhanced in concert with a reduction in fishing intensity to maintain effective conservation measures that promote increased resilience of fisheries to climate change and other stressors.

A Review of the Production, Recycling and Management of Marine Plastic Pollution - Ibrahim Issifu; U. Rashid Sumaila (Journal of Marine Science and Engineering, 2020)
The human attachment to plastic has intensified recently due to its lightweight, versatility, low-cost and durability and so has the damage to the marine environment as marine plastic pollution has correspondingly increased. As a result, there has been increasing concern on the issue of marine plastic pollution. Policy-based organizations such as the United Nations Environment Programme have drawn public attention to the scope, magnitude and impacts of marine pollution in recent decades. Research on marine pollution can play a significant role in contributing to policy-making processes in support of the United Nations Sustainable Development Goal on Life Below Water (SDG 14), by providing scientific analysis on the effects and sources of marine plastic pollution. This paper provides a theoretical and empirical overview of marine plastic pollution and its potential effects on marine ecosystems. It also discusses SDGs that are relevant to marine plastic pollution and suggest priorities for further research.